Characterization of β-Ketoacyl-Acyl Carrier Protein Synthase III from Streptomyces glaucescens and Its Role in Initiation of Fatty Acid Biosynthesis - Han, Lei (American Society for Microbiology, 1998)
The Streptomyces glaucescens fabH gene, encoding β-ketoacyl-acyl carrier protein (β-ketoacyl-ACP) synthase (KAS) III (FabH), was overexpressed in Escherichia coli, and the resulting gene product was purified to homogeneity by metal chelate chromatography. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis of the purified protein revealed an M(r) of 37,000, while gel filtration analysis determined a native M(r) of 72,000 ± 3,000 (mean ± standard deviation), indicating that the enzyme is homodimeric. The purified recombinant protein demonstrated both KAS activity and acyl coenzyme A (acyl-CoA):ACP transacylase (ACAT) activity in a 1:0.12 ratio. The KAS and ACAT activities were both sensitive to thiolactomycin inhibition. The KAS activity of the protein demonstrated a K(m) value of 3.66 μM for the malonyl-ACP substrate and an unusual broad specificity for acyl-CoA substrates, with K(m) values of 2.4 μM for acetyl-CoA, 0.71 μM for butyryl-CoA, and 0.41 μM for isobutyryl-CoA. These data suggest that the S. glaucescens FabH is responsible for initiating both straight- and branched-chain fatty acid biosynthesis in Streptomyces and that the ratio of the various fatty acids produced by this organism will be dictated by the ratios of the various acyl-CoA substrates that can react with FabH. Results from a series of in vivo directed biosynthetic experiments in which the ratio of these acyl-CoA substrates was varied are consistent with this hypothesis. An additional set of in vivo experiments using thiolactomycin provides support for the role of FabH and further suggests that a FabH-independent pathway for straight-chain fatty acid biosynthesis operates in S. glaucescens.